Inventory management practices impact on gross profit margin: A study on beverage, food and tobacco sector listed companies of Sri Lanka - Sritharan, V. (EAISR International Academic Conferences Proceedings, 2019)
Inventory is a vital part of current assets and huge funds are committed to inventories as to ensure smooth flow of production and to meet consumer demand. Effective and efficient in ventory management goes a long way in survival of a business firm. And Inventory manage ment plays an essential role in balancing the benefits and cost associated with holding inven tory. So this study investigate inventory management practices effects on gross profit margin of the companies in beverage food and tobacco sector, Sri Lanka Colombo stock exchange. A panel data from 2012 to 2016 was gathered for the analysis from the annual reports of 20 bev erage food and tobacco sector firms considered. The multiple regression model was applied in the data analysis to find out the relationship between inventory management practices and gross profit margin. The variables used include inventory conversion period, operating cycle, current ratio, cash conversion cycle and gross profit margin. The results provide that invento ry conversion periods, operating cycle have a significant positive relationship with gross prof it margin whereas cash conversion cycle has negative relationship with gross profit margin. In addition to that, inventory management has significant impact on the profitability measures of gross profit margin.
Keywords: Inventory Management; Beverage Food and Tobacco sector; Gross profit margin